MENGEMBANGKAN UMKM KELOMPOK WANITA TANI DALAM TRANSFORMASI DIGITAL MELALUI APLIKASI SHOPEE - Muthoharoh, Muthoharoh; Putri, Amelia; Riana; Yuliany; Husain Al-Idrus, Muhammad; Mubarok, Farhan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
With digital transformation, global MSMEs must adopt technology, especially digital marketing. However, some MSMEs do not take full advantage of it. In Indonesia, the growth of MSMEs is hampered by a lack of resources and poor marketing skills. Performance is influenced by digital marketing and market capabilities, while rebranding is an important strategy in digital marketing. It is proven that digital marketing through media such as the web, Shopee, TikTok and Instagram is very important for the growth of small and medium businesses (MSMEs). This training was designed to solve the problems faced by members of the Ratu Arimbi women's farmer group in SusukanTonggoh Village, Susukan Lebak District, Cirebon Regency. Members of the KWT Ratu Arimbi group faced difficulties in marketing processed purple sweet potato cumin products during the Covid-19 pandemic.